Water-based liquid ink, printed matter printed with said water-based liquid ink, and greaseproof paper
A water-based ink using polysaccharides and styrene-acrylic resins addresses adhesion and oil resistance issues in water-based inks, maintaining whiteness and achieving high biomass content, suitable for food and sanitary packaging.
Patent Information
- Application Number
- JP2020209101
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-17
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2040-12-17
AI Technical Summary
Existing water-based inks for paper containers face issues with adhesion, oil resistance, and color tone when using rosin-derived raw materials, particularly when aiming for a biomass content of 10% or more, which affect whiteness and adhesion on coated or laminated papers.
A water-based liquid ink composition using non-rosin materials, specifically polysaccharides and styrene-acrylic resins as binders, to maintain whiteness and improve adhesion and oil resistance.
The ink achieves high adhesion and excellent oil resistance without impairing whiteness, suitable for food and sanitary packaging, while using at least 10% biomass raw materials, ensuring environmental friendliness and safety.
Smart Images

Figure 0007608144000001 
Figure 0007608144000002 
Figure 0007608144000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an aqueous liquid ink composition that can be used in aqueous gravure printing and aqueous flexographic printing. [Background technology]
[0002] In recent years, biomass raw materials have been attracting attention as carbon-neutral materials against the backdrop of global warming and the depletion of petroleum resources. In response to this, the environment surrounding inks is also changing from moment to moment, and biomass inks are currently being actively developed. Products that use a certain amount of biomass raw materials can be certified as biomass by the Organic Resources Association, so the industry is demanding products that contain 10% or more of biomass raw materials in the solid content, i.e., a biomass degree of 10 or more.
[0003] In the field of water-based inks for paper containers, including paper food containers, several biomass inks have also been developed (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-108529 A Summary of the Invention [Problem to be solved by the invention]
[0005] The water-based ink for paper containers described in Patent Document 1 uses a raw material derived from rosin, which is alkali-soluble and easy to make water-based. However, since the raw material derived from rosin has a strong color and a high acid value, the following three problems arise when it is mixed into an ink. The first problem is the adverse effect on the color of white and light colors. Since rosin has a hue of dark yellowish brown to brown, when attempting to achieve a biomass degree of 10 or more, the color derived from rosin becomes prominent. This is a problem, especially in white colors, as it causes a loss of whiteness.
[0006] The second problem is the decrease in adhesion due to the acid value. While this is often not a problem with uncoated paper, which the ink penetrates easily, for papers that are relatively difficult for the ink to penetrate, such as coated paper, poly-coated paper, and polyethylene-laminated paper, a high ink acid value significantly reduces adhesion. The third problem is oil resistance. Rosin has an oleophilic skeleton, which gives it a high affinity with oils such as salad oil. As a result, when it comes to food containers, the ink coating dissolves when oil adheres to it, which is an issue. Therefore, there is a demand for the development of a water-based ink that solves all of these problems and at the same time uses more than 10% biomass raw materials in the solids content.
[0007] Therefore, the problem that the present invention aims to solve is to provide an aqueous liquid ink composition that uses biomass raw materials, does not impair the whiteness of the ink, has high adhesion to substrates, and has excellent oil resistance. [Means for solving the problem]
[0008] The present inventors conducted extensive research to solve the above problems, and developed a water-based ink that uses a non-rosin-based biomass raw material, i.e., a polysaccharide and a styrene-acrylic resin as a binder, thereby succeeding in obtaining properties that could not be obtained with inks of the prior art that used rosin-based materials. That is, the present invention relates to a water-based liquid ink containing a binder having a constituent portion of a styrene-(meth)acrylic copolymer (A) and a constituent portion of a polysaccharide (B), and a wax (C).
[0009] The present invention also relates to a coated material obtained by printing a base material with an aqueous liquid ink containing a binder having a styrene-(meth)acrylic copolymer (A) component portion and a polysaccharide (B) component portion, and a wax (C).
[0010] The present invention also relates to an greaseproof paper produced by printing an aqueous liquid ink containing a binder having a styrene-(meth)acrylic copolymer (A) component portion and a polysaccharide (B) component portion, and a wax (C) on a paper base material. Effect of the Invention
[0011] The aqueous liquid ink composition of the present invention uses a biomass raw material, and yet has high adhesion to a substrate and excellent oil resistance without impairing the whiteness of the ink. According to the present invention, an aqueous liquid ink composition can be obtained that uses 10% or more of a biomass raw material, yet has high adhesion, oil resistance, and water resistance without impairing the whiteness of the ink, and thus an ink composition that is environmentally friendly and highly safe for use on food products can be obtained. The ink composition of the present invention is useful as an ink for packaging, containers, and oil-resistant paper for food and sanitary products. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The water-based liquid ink of the present invention contains a binder having a styrene-(meth)acrylic copolymer (A) portion and a polysaccharide (B) portion, and a wax (C).
[0013] <Binder> The binder of the present invention has a styrene-(meth)acrylic copolymer (A) as a constituent portion and a polysaccharide (B) as a constituent portion. The binder may have a component part of the styrene-(meth)acrylic copolymer (A) and a component part of the polysaccharide (B). For example, the binder may contain the styrene-(meth)acrylic copolymer (A) and the polysaccharide (B) separately, or may contain the styrene-(meth)acrylic copolymer (A) in a bonded form (complex of the styrene-(meth)acrylic copolymer (A) and the polysaccharide (B)) such as a styrene-(meth)acrylic copolymer (A) to which a modified polysaccharide (B) has been added, or may contain the styrene-(meth)acrylic copolymer (A), the polysaccharide (B), and a complex of the styrene-(meth)acrylic copolymer (A) and the polysaccharide (B), or may contain the styrene-(meth)acrylic copolymer (A) and a complex of the styrene-(meth)acrylic copolymer (A) and the polysaccharide (B), or may contain the polysaccharide (B) and a complex of the styrene-(meth)acrylic copolymer (A) and the polysaccharide (A), or may contain the polysaccharide (B) and a complex of the styrene-(meth)acrylic copolymer (A) and the polysaccharide (B).
[0014] (Styrene-(meth)acrylic copolymer (A)) The styrene-(meth)acrylic copolymer (A) used in the present invention refers to a copolymer containing a styrene monomer and a (meth)acrylic monomer as raw material monomers. Therefore, it may be a copolymer of general-purpose monomers such as a styrene monomer and a (meth)acrylic monomer.
[0015] Examples of the styrene monomer include alkylstyrenes such as styrene, α-methylstyrene, β-methylstyrene, 2,4-dimethylstyrene, α-ethylstyrene, α-butylstyrene, and α-hexylstyrene, halogenated styrenes such as 4-chlorostyrene, 3-chlorostyrene, and 3-bromostyrene, and further styrene monomers such as 3-nitrostyrene, 4-methoxystyrene, and vinyltoluene. Among these, it is particularly preferable to use styrene monomers such as styrene, α-methylstyrene, and tert-butylstyrene.
[0016] Examples of the (meth)acrylic monomer include methyl acrylate, methyl methacrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, sec-butyl acrylate, tert-butyl acrylate, 2-ethylbutyl acrylate, 1,3-dimethylbutyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, octyl acrylate, ethyl methacrylate, n-butyl methacrylate, 2-methylbutyl methacrylate, pentyl methacrylate, heptyl methacrylate, nonyl methacrylate, ethyl carbitol acrylate, 3-ethoxypropyl acrylate, 3-ethoxybutyl acrylate, diethyl methacrylate, ... Examples of the monomer include aryl acrylates and aralkyl acrylates such as methylaminoethyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxybutyl acrylate, ethyl-α-(hydroxymethyl)acrylate, dimethylaminoethyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, phenyl acrylate, benzyl acrylate, phenylethyl acrylate, and phenylethyl methacrylate; and monoacrylates or monomethacrylates of polyhydric alcohols such as diethylene glycol, triethylene glycol, polyethylene glycol, glycerin, and bisphenol A. One or more of these monomers can be added as the monomer component.
[0017] Also, maleic acid, maleic anhydride, maleic acid dialkyl esters such as dimethyl maleate and diethyl maleate, vinyl acetate, etc., which are copolymerizable with the (meth)acrylic monomer, can be copolymerized.
[0018] From the viewpoint of water dispersibility or water solubility, the styrene-acrylic copolymer used in the present invention preferably contains an anionic group such as a carboxyl group, a sulfonic acid group, or a phosphoric acid group. Among these, it is preferable that the copolymer contains a carboxyl group from the viewpoint of stability and other points of view. The anionic group can be introduced by copolymerizing a monomer having an anionic group, such as (meth)acrylic acid, with another ethylenically unsaturated monomer copolymerizable therewith. In the present invention, (meth)acrylic is a general term for acrylic and methacrylic, and (meth)acrylic acid is a general term for acrylic acid and methacrylic acid. The same applies to various esters of (meth)acrylic acid. In the present invention, acrylic acid and methacrylic acid may be used alone or in combination.
[0019] The copolymer used in the present invention may be a linear copolymer consisting only of polymerization units of monoethylenically unsaturated monomers, or a copolymer containing a partially crosslinked portion obtained by copolymerizing a very small amount of various crosslinkable ethylenically unsaturated monomers.
[0020] Examples of such ethylenically unsaturated monomers having crosslinking properties include glycidyl (meth)acrylate, divinylbenzene, and poly(meth)acrylates of polyhydric alcohols such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, poly(oxyethyleneoxypropylene) glycol di(meth)acrylate, and tri(meth)acrylate of an alkylene oxide adduct of glycerin.
[0021] In the present invention, the reaction rate of each monomer used is considered to be approximately the same, and the charge ratio of each monomer is considered to be the content ratio of the polymerized unit of each monomer in terms of mass. The copolymer in the present invention can be synthesized by various conventionally known reaction methods such as bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization. In this case, a known and commonly used polymerization initiator, a chain transfer agent (polymerization degree regulator), a surfactant, and an antifoaming agent suitable for each polymerization method can be used in combination. For example, peroxides, persulfates, azo compounds, redox systems, or mixtures thereof may be used. Examples of peroxides include hydrogen peroxide, ammonium peroxide, sodium peroxide, potassium peroxide, t-butyl peroxide, t-butyl hydroperoxide, cumene hydroperoxide, and benzene peroxide. Examples of persulfates include ammonium persulfate, sodium persulfate, and potassium persulfate.
[0022] Examples of the azo compound include 2,2-azobisisobutyronitrile and 4,4'-(4-cyanovaleric acid). The redox system is composed of an oxidizing agent and a reducing agent, and examples of the oxidizing agent include one of the above-mentioned peroxides, persulfates, or azo compounds, or sodium or potassium chloride, or sodium or potassium bromide. Examples of the reducing agent include ascorbic acid, glucose, or ammonium, sodium or potassium hydrogen sulfate, sodium or potassium hydrogen sulfite, sodium or potassium thiosulfate, sodium or potassium sulfide, or iron(II) ammonium sulfate.
[0023] The styrene-acrylic copolymer may be a random copolymer or a graft copolymer. An example of the graft copolymer is a graft copolymer in which a copolymer of styrene and a nonionic monomer copolymerizable with polystyrene or styrene serves as the trunk or branch, and a copolymer of acrylic acid, methacrylic acid, and other monomers including styrene serves as the branch or trunk. The styrene-acrylic copolymer may be a mixture of this graft copolymer and a random copolymer.
[0024] In the present invention, the weight average molecular weight of the styrene-acrylic copolymer is preferably within a range of 5,000 to 500,000, and more preferably within a range of 8,000 to 300,000. The weight average molecular weight here is a value measured by GPC (gel permeation chromatography) method, and is a value converted into the molecular weight of polystyrene used as a standard substance.
[0025] The acid value of the styrene-acrylic copolymer used in the present invention is preferably 1 to 250 mgKOH / g, more preferably 1 to 200 (mgKOH / g), more preferably 1 to 150 (mgKOH / g), more preferably 1 to 100 (mgKOH / g), and even more preferably 1 to 50 (mgKOH / g). The acid value here is a value measured according to the Japanese Industrial Standards "K 0070:1992. Testing method for acid value, saponification value, ester value, iodine value, hydroxyl value and unsaponifiable matter of chemical products", and is the amount (mg) of potassium hydroxide required to completely neutralize 1 g of resin.
[0026] (Basic compounds) In the present invention, the anionic group of the styrene-acrylic copolymer is preferably neutralized. Known basic compounds can be used for neutralization, such as inorganic basic compounds such as hydroxides of alkali metals such as potassium and sodium; carbonates of alkali metals such as potassium and sodium; carbonates of alkaline earth metals such as calcium and barium; ammonium hydroxide, and organic basic compounds such as amino alcohols such as ammonia, triethanolamine, N,N-dimethanolamine, N-aminoethylethanolamine, dimethylethanolamine, and N-butyldiethanolamine, morpholines such as morpholine, N-methylmorpholine, and N-ethylmorpholine, and piperazines such as N-(2-hydroxyethyl)piperazine and piperazine hexahydrate. Among them, ammonia and alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, and lithium hydroxide are preferred. Neutralization makes the styrene-acrylic copolymer water-dispersible or water-soluble.
[0027] The glass transition temperature (hereinafter sometimes referred to as Tg) of the styrene-acrylic copolymer is preferably in the range of -40°C to 40°C, more preferably in the range of -35°C to 35°C, more preferably in the range of -30°C to 30°C, and still more preferably in the range of -25°C to 20°C.
[0028] In the present invention, the glass transition temperature is obtained by measurement using a differential scanning calorimeter.
[0029] There are preferred ranges for the acid value and the glass transition temperature, and for example, when the styrene-acrylic copolymer is an aqueous solution, it is preferred that the acid value is 100 to 250 mgKOH / g and the glass transition temperature is -40 to 40°C. If the acid value is 100 mgKOH / g or more, the solubility tends to be maintained, and if the acid value is 250 mgKOH / g or less, the solubility tends to be maintained. In addition, if the glass transition temperature is -30°C or more, the heat resistance tends to be maintained, and if the glass transition temperature is 40°C or less, the film-forming property tends to be maintained.
[0030] On the other hand, when the styrene-acrylic copolymer is in the form of a water dispersion, it is preferable that the acid value is 1 to 200 mgKOH / g and the glass transition temperature is -40 to 40°C. If the acid value is 1 mgKOH / g or more, dispersibility tends to be maintained, and if the acid value is 200 mgKOH / g or less, dispersibility tends to be maintained. In addition, if the glass transition temperature is -30°C or more, heat resistance tends to be maintained, and if the glass transition temperature is 40°C or less, film-forming properties tend to be maintained.
[0031] When a mixture of an aqueous solution and an aqueous dispersion is used, the glass transition temperature of the styrene-acrylic resin is preferably −40 to 40° C. If the glass transition temperature is −30° C. or higher, heat resistance tends to be maintained, and if the content of the styrene-acrylic copolymer is in the range of 3 to 50 mass% in terms of non-volatile matter and the glass transition temperature is 40° C. or lower, film-forming properties tend to be maintained.
[0032] The amount of the styrene-acrylic copolymer (A) is preferably within a range of 3 to 70 mass %, and more preferably 5 to 60 mass %, calculated as solid content, based on the total amount of the water-based liquid ink composition of the present invention.
[0033] When the content of the styrene-acrylic copolymer is 3% by mass or more in terms of non-volatile content, dispersibility tends to be maintained, and when the content of the styrene-acrylic copolymer is 70% by mass or less in terms of non-volatile content, heat resistance and abrasion resistance tend to be maintained.
[0034] The styrene-acrylic copolymer (A) has a lower limit of 10 mass%, preferably 20 mass%, preferably 30 mass%, and preferably 40 mass%, in terms of the solids weight ratio in the ink, and an upper limit of 90 mass%, preferably 80 mass%, and preferably 70 mass%, in terms of the solids weight ratio in the ink.
[0035] (Polysaccharide (B)) Examples of the polysaccharide (B) used in the present invention include carrageenan, galactomannan, xanthan gum alginate, pectin, xylan, glucomannan, pullulan, curdlan, cellulose, cellulose derivatives, carboxymethylcellulose (CMC), starch, starch derivatives, corn starch, etc. These may be used alone or in combination of two or more of them as appropriate. Among them, starch, starch derivatives, and corn starch are preferred.
[0036] In the present invention, the weight average molecular weight of the polysaccharide is preferably within the range of 5,000 to 5,000,000. Here, the weight average molecular weight is a value measured by GPC (gel permeation chromatography) method, and is a value converted into the molecular weight of polystyrene used as a standard substance.
[0037] These polysaccharides have a hue close to white, so they do not affect the color of the ink. In addition, because polysaccharides have a low acid value, they do not adversely affect adhesion even when using paper that is difficult for ink to penetrate as a substrate. In addition, because they have many hydroxyl groups in their structure, they are highly hydrophilic and have excellent oil resistance. Furthermore, the physical properties such as water resistance and oil resistance of the polysaccharide (B) can be adjusted by adding and / or introducing functional groups to some of the hydroxyl groups. For example, water resistance can be improved by adding and / or introducing hydrophobic functional groups.
[0038] The polysaccharide may be a reaction product obtained by reacting raw material monomers, such as a styrene monomer and an acrylic monomer, with the polysaccharide in the presence of each other during the production of the styrene-acrylic copolymer (in this case, it can be expected that the polysaccharide will be incorporated into the polymer chain as a copolymerization component of the styrene-acrylic copolymer in some cases), or the polysaccharide may be further mixed as appropriate with the emulsion in which the polymerization reaction of the styrene-acrylic copolymer has been completed.
[0039] The amount of the polysaccharide (B) added is preferably within a range of 10 to 80 mass %, and more preferably 15 to 70 mass %, calculated as solid content, based on the total amount of the water-based liquid ink composition of the present invention.
[0040] The lower limit of the solids weight ratio of the polysaccharide (B) in the ink is preferably 5 mass%, more preferably 10 mass%, and more preferably 15 mass%, and the upper limit of the solids weight ratio in the ink is preferably 80 mass%, more preferably 70 mass%, and more preferably 60 mass%.
[0041] The mass ratio of the styrene-(meth)acrylic copolymer (A) and the polysaccharide (B) is preferably 10:1 to 1:2, and more preferably 5:1 to 1:1. The higher the ratio of the polysaccharide (B), the higher the ratio of the biomass component in the ink can be, and the more the oil resistance, oil-rubbing resistance, etc. can be improved. On the other hand, the higher the ratio of the styrene-(meth)acrylic copolymer (A), the more the pigment dispersibility, film-forming properties, water resistance, water-rubbing resistance, etc. can be improved.
[0042] The binder of the present invention may be a composite of (A) and (B), such as a styrene-(meth)acrylic copolymer (A) having a polysaccharide (B) added thereto. By using such a composite, an ink composition having an excellent balance of various properties such as dispersibility, film-forming property, water resistance, and oil resistance can be obtained. The styrene-(meth)acrylic copolymer (A) having a polysaccharide (B) added thereto can be obtained by a known method, for example, as described above, by first allowing raw material monomers such as a styrene monomer and an acrylic monomer to coexist with a modified polysaccharide, and then reacting them to incorporate the polysaccharide into the polymer chain as a copolymerization component of the styrene-acrylic copolymer.
[0043] Known modified polysaccharides can be used, and examples thereof include modified starch obtained by bonding an aliphatic saturated hydrocarbon group, an aliphatic unsaturated hydrocarbon group, an aromatic hydrocarbon group, or the like to the above-mentioned polysaccharide (B) via an ester bond and / or an ether bond. The modified polysaccharide is preferably esterified.
[0044] In the total amount of the binder of the present invention, the binder having a styrene-(meth)acrylic copolymer (A) component portion and a polysaccharide (B) component portion is preferably contained in an amount of 60 mass% or more, and more preferably 70 mass% or more.
[0045] (Other components: binder resin) In the present invention, the styrene-(meth)acrylic copolymer (A) acts as the main binder resin, but if necessary, a water-dispersible or water-soluble resin other than the styrene-(meth)acrylic copolymer (A) may be used in combination. For example, the binder resin is not particularly limited, and may be an acrylic copolymer such as a urethane resin, polyvinyl alcohols, polyvinylpyrrolidones, polyacrylic acid, acrylic acid-acrylonitrile copolymer, potassium acrylate-acrylonitrile copolymer, vinyl acetate-acrylic acid ester copolymer, or acrylic acid-acrylic acid alkyl ester copolymer, which are used in general water-based liquid printing inks; styrene-maleic acid; styrene-maleic anhydride; vinyl naphthalene-acrylic acid copolymer; vinyl naphthalene-maleic acid copolymer; vinyl acetate-ethylene copolymer, vinyl acetate-fatty acid vinyl ethylene copolymer, vinyl acetate-maleic acid ester copolymer, vinyl acetate-crotonic acid copolymer, or vinyl acetate-acrylic acid copolymer, or a vinyl acetate copolymer or a salt thereof. These may also be used in combination as appropriate according to the desired physical properties. Among them, as the binder resin, it is preferable to use an acrylic resin or a urethane resin, since these are easily available.
[0046] The acrylic resin is not particularly limited, and examples thereof include homopolymerization or copolymerization of (meth)acrylate, and copolymerization of vinyl monomer copolymerizable with (meth)acrylate. However, in this specification, the "copolymer copolymerized with vinyl monomer copolymerizable with (meth)acrylate" contained as another component does not include styrene-(meth)acrylic copolymer (A). In addition, it is preferable that the (meth)acrylic copolymer has an acid value for the purpose of imparting water dispersibility or water solubility.
[0047] Examples of vinyl monomers copolymerizable with (meth)acrylates include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, isopropyl (meth)acrylate, and isobutyl (meth)acrylate; aromatic (meth)acrylates such as benzyl (meth)acrylate; hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate; alkyl polyalkylene glycol mono(meth)acrylates such as methoxypolyethylene glycol mono(meth)acrylate and methoxypolypropylene glycol mono(meth)acrylate; fluorine-based (meth)acrylates such as perfluoroalkylethyl (meth)acrylate; aromatic vinyl compounds such as vinyl naphthalene, vinyl anthracene, and 1,1-diphenylethylene; glycidyl (meth)acrylate, epoxy (meth)acrylate, ethylene glycol di(meth)acrylate, diethylene (Meth)acrylates such as glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylene glycol tetra(meth)acrylate, 2-hydroxy-1,3-diacryloxypropane, 2,2-bis[4-(acryloxymethoxy)phenyl]propane, 2,2-bis[4-(acryloxyethoxy)phenyl]propane, dicyclopentenyl(meth)acrylate, tricyclodecanyl(meth)acrylate, tris(acryloxyethyl)isocyanurate, and urethane(meth)acrylate. Examples of the monomer include acrylate compounds, (meth)acrylates having an alkylamino group such as dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, and dimethylaminopropyl (meth)acrylate, vinylpyridine compounds such as 2-vinylpyridine, 4-vinylpyridine, and naphthylvinylpyridine, and conjugated dienes such as 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, and 1,3-cyclohexadiene. These monomers can be used alone or in combination of two or more.
[0048] In addition, for the purpose of introducing one or more acidic groups selected from the group consisting of carboxyl groups and carboxylate groups in which the carboxyl groups are neutralized with a basic compound, a copolymer having an acid value can be obtained by copolymerizing a (meth)acrylic monomer having a carboxyl group, such as (meth)acrylic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid, β-(meth)acryloyloxyethyl hydrogen succinate, or β-(meth)acryloyloxyethyl hydrogen phthalate. When introducing an acidic group, it is preferable to appropriately adjust the amount of the monomer so that the acid value is in the desired range.
[0049] The copolymer can be produced, for example, by polymerizing various monomers in the presence of a polymerization initiator at a temperature range of 50°C to 180°C, more preferably at a temperature range of 80°C to 150°C. Examples of the polymerization method include bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization. Examples of the polymerization mode include random copolymers, block copolymers, and graft copolymers. The copolymer used in the present invention may be a core-shell type.
[0050] The acid value of the (meth)acrylic copolymer is preferably 1 mgKOH / g or more and 250 mgKOH / g or less, more preferably 10 mgKOH / g or more and 240 mgKOH / g or less, and even more preferably 20 mgKOH / g or more and 230 mgKOH / g or less. If the acid value is 250 mgKOH / g or less, water resistance and water-friction resistance can be improved.
[0051] The weight-average molecular weight of the (meth)acrylic copolymer is preferably in the range of 5,000 to 500,000. If the weight-average molecular weight is 5,000 or more, the heat resistance of the resin film is not reduced, and the laminate tends to maintain its abrasion resistance and water abrasion resistance. If the weight-average molecular weight is 500,000 or less, adhesion to the substrate and scratch resistance tend to be both achieved.
[0052] The glass transition temperature (Tg) of the (meth)acrylic copolymer is preferably in the range of −40° C. to 100° C. If the Tg of the copolymer is −40° C. or higher, the film strength is maintained and the water friction resistance of the laminate is not reduced, and if it is 100° C. or lower, the abrasion resistance, water friction resistance, and scratch resistance of the laminate tend to be well maintained.
[0053] The glass transition temperature (Tg) refers to a so-called calculated glass transition temperature, and refers to a value calculated by the following method. (Formula 1) 1 / Tg(K)=(W1 / T1)+(W2 / T2)+...(Wn / Tn) (Equation 2) Tg(℃)=Tg(K)-273 In formula 1, W1, W2, ...Wn represent the mass% of each monomer relative to the total mass of the monomers used in the production of the polymer, and T1, T2, ...Tn represent the glass transition temperature (K) of the homopolymer of each monomer. The values of T1, T2, ...Tn are taken from Polymer Handbook (Fourth Edition, edited by J. Brandrup, EH Immergut, EA Grulke).
[0054] In addition, the glass transition temperature of homopolymers of each monomer, which are not described in the Polymer Handbook, was measured using a differential scanning calorimeter "DSC Q-100" (manufactured by TA Instruments) according to a method conforming to JIS K7121. Specifically, the polymer from which the solvent was completely removed by vacuum suction was subjected to measurement of the change in heat quantity in the range of -100°C to +200°C at a heating rate of 20°C / min, and the point where a straight line equidistant in the vertical direction from the straight line extended from each baseline intersects with the curve of the stepwise change in the glass transition was determined as the glass transition temperature.
[0055] The binder resin other than the styrene-(meth)acrylic copolymer (A) is preferably contained in an amount of 0.5 to 40 mass %, and more preferably 1 to 30 mass %, calculated as solid content, based on the total amount of the water-based liquid ink composition of the present invention.
[0056] As the binder resin, it is preferable to use a binder having a styrene-(meth)acrylic copolymer (A) component portion and a polysaccharide (B) component portion in combination with the above-mentioned (meth)acrylic copolymer, and it is more preferable to use a binder having a styrene-(meth)acrylic copolymer (A) component portion and a polysaccharide (B) component portion in combination with a (meth)acrylic copolymer having a glass transition temperature in the range of -40°C to 100°C and an acid value in the range of 1 to 250 mgKOH / g. In the total amount of binders in the aqueous liquid ink of the present invention, the proportion of the binder having a styrene-(meth)acrylic copolymer (A) component portion and a polysaccharide (B) component portion, and the total amount of the (meth)acrylic copolymer as described above, is preferably 70 mass % or more, more preferably 80 mass % or more, and more preferably 90 mass % or more.
[0057] <Lubricant (C)> The water-based liquid printing ink of the present invention contains a lubricant (C). By containing the lubricant (C), it is possible to improve the abrasion resistance, water abrasion resistance, slippage, etc. Examples of the lubricant (C) include wax, organic fine particles, inorganic fine particles, and organic-inorganic composite fine particles. Examples of inorganic fine particles include zirconia, barium sulfate, calcium carbonate, titanium oxide, etc. Examples of organic fine particles include resin beads using urethane resin, acrylic resin, melamine resin, etc. Examples of organic-inorganic composite fine particles include acrylic-silicon and silicone fine particles. Among them, it is preferable to use wax or silicone fine particles.
[0058] As the wax, known waxes can be used, among which carbon-based waxes are preferred. Examples of carbon waxes include liquid paraffin, natural paraffin, synthetic paraffin, microcrystalline wax, polyethylene wax, fluorocarbon wax, ethylene-propylene copolymer wax, tetrafluoroethylene resin wax, Fischer-Tropsch wax, etc. These waxes may be used alone or in combination of two or more. The total amount of the lubricant (C) added is preferably 0.5 to 5 mass% of the total amount of the aqueous liquid ink composition. When the total amount of the lubricant (C) added is 0.5 mass% or more of the total amount of the ink, the abrasion resistance, water-resistant abrasion resistance, and scratch resistance can be maintained. When the total amount of the lubricant (C) added is 5 mass% or less of the total amount of the liquid ink composition, the adhesion to the substrate, abrasion resistance, water-resistant abrasion resistance, and scratch resistance can be maintained.
[0059] The lubricant (C) preferably has an average particle size in the range of 3 to 7 μm and a softening point of 100 to 350° C. If the average particle size is 3 μm or more, abrasion resistance is maintained, and if it is 7 μm or less, dispersibility tends to be maintained. Also, if the softening point is 100° C. or more, heat resistance tends to be maintained.
[0060] <Coloring agent> Colorants used in the aqueous liquid printing ink of the present invention include inorganic pigments, organic pigments, or dyes that are used in general inks, paints, and recording agents, etc. Examples of organic pigments include soluble azo-based, insoluble azo-based, azo-based, phthalocyanine-based, halogenated phthalocyanine-based, anthraquinone-based, anthanthrone-based, dianthraquinonyl-based, anthrapyrimidine-based, perylene-based, perinone-based, quinacridone-based, thioindigo-based, dioxazine-based, isoindolinone-based, quinophthalone-based, azomethine azo-based, flavanthrone-based, diketopyrrolopyrrole-based, isoindoline-based, indanthrone-based, carbon black-based, and other pigments. In addition, for example, carmine 6B, lake red C, permanent red 2B, disazo yellow, pyrazolone orange, carmine FB, chromophthal yellow, chromophthal red, phthalocyanine blue, phthalocyanine green, dioxazine violet, quinacridone magenta, quinacridone red, indanthrone blue, pyrimidine yellow, thioindigo bordeaux, thioindigo magenta, perylene red, perinone orange, isoindolinone yellow, aniline black, diketopyrrolopyrrole red, daylight fluorescent pigments, etc. can be mentioned. In addition, both non-acid-treated pigments and acid-treated pigments can be used. Specific examples of preferred organic pigments are given below.
[0061] Examples of black pigments include CI Pigment Black 1, CI Pigment Black 6, CI Pigment Black 7, CI Pigment Black 9, and CI Pigment Black 20.
[0062] Examples of indigo pigments include CI Pigment Blue 15, CI Pigment Blue 15:1, CI Pigment Blue 15:2, CI Pigment Blue 15:3, CI Pigment Blue 15:4, CI Pigment Blue 15:5, CI Pigment Blue 15:6, CI Pigment Blue 16, CI Pigment Blue 17:1, CI Pigment Blue 22, CI Pigment Blue 24:1, CI Pigment Blue 25, CI Pigment Blue 26, CI Pigment Blue 60, CI Pigment Blue 61, CI Pigment Blue 62, CI Pigment Blue 63, CI Pigment Blue 64, CI Pigment Blue 75, CI Pigment Blue 79, and CI Pigment Blue 80.
[0063] Examples of green pigments include CI Pigment Green 1, CI Pigment Green 4, CI Pigment Green 7, CI Pigment Green 8, CI Pigment Green 10, and CI Pigment Green 36.
[0064] Examples of red pigments include CI Pigment Red 1, CI Pigment Red 2, CI Pigment Red 3, CI Pigment Red 4, CI Pigment Red 5, CI Pigment Red 6, CI Pigment Red 7, CI Pigment Red 8, CI Pigment Red 9, CI Pigment Red 10, CI Pigment Red 11, CI Pigment Red 12, CI Pigment Red 15, CI Pigment Red 16, CI Pigment Red 17, CI Pigment Red 18, CI Pigment Red 19, CI Pigment Red 20, CI Pigment Red 21, CI Pigment Red 22, CI Pigment Red 23, CI Pigment Red 24, CI Pigment Red 25, CI Pigment Red 26, CI Pigment Red 27, CI Pigment Red 28, CI Pigment Red 29, CI Pigment Red 30, CI Pigment Red 31, CI Pigment Red 32, CI Pigment Red 33, CI Pigment Red 34, CI Pigment Red 35, CI Pigment Red 36, CI Pigment Red 37, CI Pigment Red 38, CI Pigment Red 39, CI Pigment Red 40, CI Pigment Red 41, CI Pigment Red 42, CI Pigment Red 43, CI Pigment Red 44, CI Pigment Red 45, CI Pigment Red 46, CI Pigment Red 47, CI Pigment Red 48, CI Pigment Red 49, CI Pigment Red 50, CI Pigment Red 51, CI Pigment Red 52, CI Pigment Red 53, CI Pig Red 19, CI Pigment Red 20, CI Pigment Red 21, CI Pigment Red 22, CI Pigment Red 23, CI Pigment Red 31, CI Pigment Red 32, CI Pigment Red 38, CI Pigment Red 41, CI Pigment Red 43, CI Pigment Red 46, CI Pigment Red 48, CI Pigment Red 48:1, CI Pigment Red 48:2, CI Pigment Red 48:3, CI Pigment Red 48:4, CI Pigment Red 48:5, CI Pigment Red 48:6, CI Pigment Red 49, CI Pigment Red 49:1, CI Pigment Red 49:2, CI Pigment Red 49:3, CI Pigment Red 52, CI Pigment Red 52:1, CI Pigment Red 52:2, CI Pigment Red 53, CI Pigment Red 53:1, CI Pigment Red 53:2, CI Pigment Red 53:3, CI Pigment Red 54, CI Pigment Red 57, CI Pigment Red 57: 1, CI Pigment Red 58, CI Pigment Red 58:1, CI Pigment Red 58:2, CI Pigment Red 58:3, CI Pigment Red 58:4, CI Pigment Red 60:1, CI Pigment Red 63, CI Pigment Red 63:1, CI Pigment Red 63:2, CI Pigment Red 63:3, CI Pigment Red 64:1, CI Pigment Red 68, CI Pigment Red 68, CI Pigment Red 81:1, CI Pigment Red 83, C.I. Pigment Red 88, CI Pigment Red 89, CI Pigment Red 95, CI Pigment Red 112, CI Pigment Red 114, CI Pigment Red 119, CI Pigment Red 122, CI Pigment Red 123, CI Pigment Red 136, CI Pigment Red 144, CI Pigment Red 146, CI Pigment Red 147, CI Pigment Red 149, CI Pigment Red 150, CI Pigment Red 164, CI Pigment Red Pigment Red 166, CI Pigment Red 168, CI Pigment Red 169, CI Pigment Red 170, CI Pigment Red 171, CI Pigment Red 172, CI Pigment Red 175, CI Pigment Red 176, CI Pigment Red 177, CI Pigment Red 178, CI Pigment Red 179, CI Pigment Red 180, CI Pigment Red 181, CI Pigment Red 182, CI Pigment Red 183, CI Pigment Red 184, CI Pigment Red 185, CI Pigment Red 187, CI Pigment Red 188, CI Pigment Red 190, CI Pigment Red 192, CI Pigment Red 193, CI Pigment Red 194, CI Pigment Red 200, CI Pigment Red 202, CI Pigment Red 206, CI Pigment Red 207, CI Pigment Red 208, CI Pigment Red 209, CI Pigment Red 210, CI Pigment Red 211, CI Pigment Red Pigment Red 213, CI Pigment Red 214, CI Pigment Red 216, CI Pigment Red 215, CI Pigment Red 216, CI Pigment Red 220, CI Pigment Red 221, CI Pigment Red 223, CI Pigment Red 224, CI Pigment Red 226, CI Pigment Red 237, CI Pigment Red 238, CI Pigment Red 239, CI Pigment Red 240, CI Pigment Red 242, CI Pigment Red 245, CIPigment Red 247, CI Pigment Red 248, CI Pigment Red 251, CI Pigment Red 253, CI Pigment Red 254, CI Pigment Red 255, CI Pigment Red 256, CI Pigment Red 257, CI Pigment Red 258, CI Pigment Red 260, CI Pigment Red 262, CI Pigment Red 263, CI Pigment Red 264, CI Pigment Red 266, CI Pigment Red 268, CI Pigment Red 269, CI Pigment Red 270, CI Pigment Red 271, CI Pigment Red 272, CI Pigment Red 279, and others.
[0065] Examples of purple pigments include CI Pigment Violet 1, CI Pigment Violet 2, CI Pigment Violet 3, CI Pigment Violet 3:1, CI Pigment Violet 3:3, CI Pigment Violet 5:1, CI Pigment Violet 13, CI Pigment Violet 19 (γ type, β type), CI Pigment Violet 23, CI Pigment Violet 25, CI Pigment Violet 27, CI Pigment Violet 29, CI Pigment Violet 31, CI Pigment Violet 32, CI Pigment Violet 36, CI Pigment Violet 37, CI Pigment Violet 38, CI Pigment Violet 42, and CI Pigment Violet 50.
[0066] Examples of yellow pigments include CI Pigment Yellow 1, CI Pigment Yellow 3, CI Pigment Yellow 12, CI Pigment Yellow 13, CI Pigment Yellow 14, Pigment Yellow 17, CI Pigment Yellow 24, CI Pigment Yellow 42, CI Pigment Yellow 55, CI Pigment Yellow 62, CI Pigment Yellow 65, CI Pigment Yellow 74, CI Pigment Yellow 83, CI Pigment Yellow 86, CI Pigment Yellow 93, CI Pigment Yellow 94, CI Pigment Yellow 95, CI Pigment Yellow 109, CI Pigment Yellow 110, CI Pigment Yellow 117, CI Pigment Yellow 120, CI Pigment Yellow 122, CI Pigment Yellow 124, CI Pigment Yellow 126, CI Pigment Yellow 128, CI Pigment Yellow 129, CI Pigment Yellow 130, CI Pigment Yellow 131, CI Pigment Yellow 132, CI Pigment Yellow 133, CI Pigment Yellow 134, CI Pigment Yellow 135, CI Pigment Yellow 136, CI Pigment Yellow 137, CI Pigment Yellow 138, CI Pigment Yellow 139, CI Pigment Yellow 140, CI Pigment Yellow 141, CI Pigment Yellow 142, CI Pigment Yellow 143, CI Pigment Yellow 144, CI Pigment Yellow 145, CI Pigment Yellow 146, CI Pigment Yellow 147, CI Pigment Yellow 148, CI Pigment Yellow 149, CI Pigment Yellow 150, CI Pigment Yellow 15 Yellow 120, Pigment Yellow 125, CI Pigment Yellow 128, CI Pigment Yellow 129, CI Pigment Yellow 137, CI Pigment Yellow 138, CI Pigment Yellow 139, CI Pigment Yellow 147, CI Pigment Yellow 148, CI Pigment Yellow 150, CI Pigment Yellow 151, CI Pigment Yellow 153, CI Pigment Yellow 154, CI Pigment Yellow 155, CI Pigment Yellow 166, CI Pigment Yellow 168, CI Pigment Yellow 174, CI Pigment Yellow 180, CI Pigment Yellow 185 and CI Pigment Yellow 213.
[0067] Examples of orange pigments include CI Pigment Orange 5, CI Pigment Orange 13, CI Pigment Orange 16, CI Pigment Orange 34, CI Pigment Orange 36, CI Pigment Orange 37, CI Pigment Orange 38, CI Pigment Orange 43, CI Pigment Orange 51, CI Pigment Range 55, CI Pigment Orange 59, CI Pigment Orange 61, CI Pigment Orange 64, CI Pigment Orange 71, and CI Pigment Orange 74.
[0068] Examples of brown pigments include CI Pigment Brown 23, CI Pigment Brown 25, and CI Pigment Brown 26.
[0069] Among them, preferred pigments include CI Pigment Black 7 as a black pigment, CI Pigment Blue 15, CI Pigment Blue 15:1, CI Pigment Blue 15:2, CI Pigment Blue 15:3, CI Pigment Blue 15:4, and CI Pigment Blue 15:6 as indigo pigments, CI Pigment Green 7 as a green pigment, and CI Pigment Red 57:1, CI Pigment Red 48:1, CI Pigment Red 48:2, CI Pigment Red 48:3, CI Pigment Red 146, CI Pigment Red 242, CI Pigment Red 185, and CI Pigment Red 12 as red pigments. Examples of pigments that can be used include CI Pigment Red 2, CI Pigment Red 178, CI Pigment Red 149, CI Pigment Red 144, CI Pigment Red 166, purple pigments such as CI Pigment Violet 23 and CI Pigment Violet 37, yellow pigments such as CI Pigment Yellow 83, CI Pigment Yellow 14, CI Pigment Yellow 180, CI Pigment Yellow 139, and orange pigments such as CI Pigment Orange 38, CI Pigment Orange 13, CI Pigment Orange 34, and CI Pigment Orange 64. It is preferable to use at least one or more pigments selected from these groups.
[0070] Examples of the inorganic pigment include carbon black, titanium oxide, zinc oxide, zinc sulfide, barium sulfate, calcium carbonate, chromium oxide, silica, red iron oxide, aluminum, and mica. In addition, a glittering pigment (Metashine; Nippon Sheet Glass Co., Ltd.) in which a metal or metal oxide is coated on a base material of glass flakes or aggregated flakes can be used. In terms of cost and coloring power, it is preferable to use titanium oxide for white ink, carbon black for black ink, aluminum for gold and silver ink, and mica for pearl ink. Aluminum is in powder or paste form, but it is preferable to use it in paste form from the standpoint of handling and safety, and whether to use leafing or non-leafing is appropriately selected from the standpoint of brightness and concentration.
[0071] The total amount of the pigments is preferably sufficient to ensure the concentration and coloring power of the ink, i.e., 1 to 60% by mass based on the total weight of the ink. The colorants may be used alone or in combination of two or more kinds. The water-based liquid ink of the present invention may further contain a solvent and other auxiliary agents according to the purpose.
[0072] <Other ingredients / auxiliaries> In addition to the above-mentioned binder and lubricant, the aqueous liquid ink composition of the present invention may contain surfactants, silica, alumina, dispersants, defoamers, leveling agents, tackifiers, preservatives, antibacterial agents, rust inhibitors, etc.
[0073] (Surfactant) The surfactant is not particularly limited and any surfactant commonly used in the art can be used. Among them, acetylene-based surfactants and alcohol alkoxylate-based surfactants are preferred.
[0074] Specific examples of the acetylene surfactant used in the present invention include 2,5-dimethyl-3-hexyne-2,5-diol, 3,6-dimethyl-4-octyne-3,6-diol, 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 3,5-dimethyl-1-hexyne-3-ol, 3-methyl-1-butyne-3-ol, 3-methyl-1-pentyne-3-ol, 3-hexyne-2,5-diol, and 2-butyne-1,4-diol. Examples of commercially available products include alkylene oxide unmodified acetylene glycol surfactants such as Surfynol 61, 82, and 104 (all manufactured by EVONIK), and alkylene oxide modified acetylene glycol surfactants such as Surfynol 420, 440, 465, 485, SE, MD-20, TG, 2502, Dynol 604, and 607 (all manufactured by EVONIK), Olfine E1004, E1010, PD-004, EXP4300, PD-501, PD-502, and SPC (all manufactured by Nissin Chemical Industry Co., Ltd.), and Acetylenol EH, E40, E60, E81, E100, and E200 (all manufactured by Kawaken Fine Chemical Co., Ltd.). Among these, alkylene oxide modified acetylene glycol surfactants are preferred.
[0075] In addition, a specific example of the alcohol alkoxylate surfactant used in the present invention is DYNWET800 (manufactured by BYK Japan Co., Ltd.) These acetylene surfactants and alcohol alkoxylate surfactants may be used alone or in combination of two or more.
[0076] The total amount of these acetylene surfactants and / or alcohol alkoxylate surfactants added is preferably 0.1 to 2% by mass of the total ink. These acetylene surfactants may be used alone or in combination of two or more. If the total amount of the acetylene surfactants and / or alcohol alkoxylate surfactants added is 0.1% by mass or more of the total ink, the wettability with the substrate is improved and the adhesion with the substrate can be maintained. If the total amount of the acetylene surfactants and / or alcohol alkoxylate surfactants added is 2% by mass or less of the total ink, the abrasion resistance, water abrasion resistance, and scratch resistance are not reduced.
[0077] Furthermore, if necessary, other acrylic polymer surfactants (for example, Polyflow WS-314 manufactured by Kyoeisha Chemical Co., Ltd.) or modified silicone surfactants (for example, Polyflow KL-401 manufactured by Kyoeisha Chemical Co., Ltd.) may be used. For the reasons mentioned above, the total amount of the surfactants used is preferably 0.1 to 2% by mass of the total amount of the ink.
[0078] The defoaming agent is added to prevent the composition from foaming when coating using various coaters. Specifically, polymer-based defoaming agents, silicon-based defoaming agents, and fluorine-based defoaming agents are preferably used. As these defoaming agents, both emulsion dispersion type and solubilization type can be used. Among them, silicon-based defoaming agents are preferred. The amount of the defoaming agent added is preferably 0.005% by weight to 2% by weight in terms of solid content based on the total amount of the aqueous liquid ink composition.
[0079] <Solvent> (Aqueous Solvent) Since the aqueous liquid ink composition of the present invention is aqueous, the solvent is mainly water, but organic solvents that are miscible with water can also be used within the range that does not impair the effects of the present invention. Examples of organic solvents that are miscible with water include alcohols such as methyl alcohol, ethyl alcohol, isopropyl alcohol, and n-propyl alcohol; polyhydric alcohols such as propylene glycol and glycerin; ethers such as propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono-n-propyl ether, and ethyl carbitol; and polyalkylene glycols such as polyethylene glycol and polypropylene glycol.
[0080] Among these, ethyl alcohol, isopropyl alcohol, polyethylene glycol, polypropylene glycol, etc. are preferred because they allow easy adjustment of drying properties. The amount of the alcohol-based solvent added is preferably 1% by mass to 4% by mass based on the total amount of the aqueous liquid ink composition. (Method for producing water-based liquid ink composition) The aqueous liquid ink composition of the present invention is produced using a bead mill, Eiger mill, sand mill, gamma mill, attritor, etc., which are generally used in the production of gravure and flexographic printing inks. Specifically, for example, the styrene-(meth)acrylic copolymer (A) and polysaccharide (B), or the reaction product obtained by reacting the styrene monomer, the acrylic monomer, and the polysaccharide together during the styrene-acrylic copolymer reaction (i.e., the styrene-(meth)acrylic copolymer (A) to which the modified polysaccharide (B) has been added), and other components are dispersed and mixed by a stirrer, and the lubricant (C) is added while continuing the stirring. Next, an antifoaming agent, a surfactant, and other auxiliary agents are added as necessary, and the mixture is dissolved and mixed by stirring with a mixer or the like to obtain the composition.
[0081] When the aqueous liquid ink composition of the present invention is used as an aqueous flexographic ink, its viscosity may be 7 to 25 seconds at 25°C using Zahn Cup #4 manufactured by Rigo Co., Ltd., and more preferably 10 to 20 seconds. The surface tension of the obtained aqueous flexographic printing ink at 25°C is preferably 25 to 50 mN / m, and more preferably 33 to 43 mN / m. The lower the surface tension of the ink, the better the ink wettability to a substrate such as a film. However, if the surface tension is less than 25 mN / m, the ink tends to spread and connect adjacent dots in halftone dots, which is likely to cause staining of the printed surface, known as dot bridging. On the other hand, if the surface tension is more than 50 mN / m, the ink wettability to a substrate such as a film decreases, which is likely to cause repelling.
[0082] On the other hand, when used as an aqueous gravure ink, the viscosity is sufficient if it is 7 to 25 seconds at 25°C using Zahn Cup #3 manufactured by Rigo Co., Ltd., and more preferably 10 to 20 seconds. The surface tension of the obtained aqueous gravure ink at 25°C is preferably 25 to 50 mN / m, and more preferably 33 to 43 mN / m, as with aqueous flexographic inks. The lower the surface tension of the ink, the better the ink's wettability to a substrate such as a film, but if the surface tension is below 25 mN / m, the ink tends to spread and connect adjacent dots in halftone dots, which is likely to cause staining of the printed surface called dot bridge. On the other hand, if the surface tension is above 50 mN / m, the ink's wettability to a substrate such as a film decreases, which is likely to cause repelling.
[0083] (Printed material) The water-based liquid ink of the present invention has excellent adhesion to various substrates and can be used for printing on paper, synthetic paper, thermoplastic resin films, plastic products, steel plates, etc.
[0084] When the aqueous liquid ink of the present invention is printed on a paper substrate, the coating method is not particularly limited, and for example, a roll coater, gravure coater, flexo coater, air doctor coater, blade coater, air knife coater, squeeze coater, impregnation coater, transfer roll coater, kiss coater, curtain coater, cast coater, spray coater, die coater, offset printing machine, screen printing machine, etc. can be used.
[0085] The paper substrate used in the water-based liquid ink of the present invention is not particularly limited, and the ink exhibits excellent adhesion even to paper substrates with low ink permeability such as coated paper. Examples of the paper substrate that can be used include high-quality paper, coated paper, art paper, imitation paper, thin paper, thick paper, and various synthetic papers used for printing catalogs, posters, flyers, CD jackets, direct mail, pamphlets, and packages for cosmetics, beverages, medicines, toys, and devices. The paper base material is manufactured by a known paper machine using natural fibers for papermaking such as wood pulp, but the papermaking conditions are not particularly specified. Examples of natural fibers for papermaking include wood pulp such as softwood pulp and hardwood pulp, non-wood pulp such as Manila hemp pulp, sisal hemp pulp, and flax pulp, and pulps obtained by chemically modifying these pulps. Types of pulp that can be used include chemical pulp produced by sulfate cooking, acidic / neutral / alkaline sulfite cooking, soda cooking, etc., ground pulp, chemi-ground pulp, thermomechanical pulp, etc.
[0086] The printed matter of the water-based liquid ink composition on a paper substrate is useful as packaging paper that requires high gloss, oil resistance, alcohol resistance, scratch resistance, etc., such as packaging materials such as bags, containers, boxes, wrapping paper, etc. that can directly contain fast food or take-out food, decorative boxes used for packaging food, medicine, cosmetics, etc., paper containers, labels, catalogs, shopping bags, book covers, posters, etc., and can be used as greaseproof paper or paper containers. In particular, the present invention uses biomass materials, so it is highly safe for the environment and the human body, and can be suitably used as a packaging material for food or hygiene. Furthermore, because of its high oil resistance and water resistance, paper coated with the water-based liquid ink of the present invention can be used as greaseproof paper and / or waterproof paper. In this case, it may be used as a water-based varnish without containing a colorant.
[0087] On the other hand, examples of the substrate film include films and laminates made of polyamide resins such as nylon 6, nylon 66, and nylon 46; polyester resins such as PET, polyethylene naphthalate, polytrimethylene terephthalate, polytrimethylene naphthalate, polybutylene terephthalate, and polybutylene naphthalate; biodegradable resins such as polyhydroxycarboxylic acids such as polylactic acid, aliphatic polyester resins such as poly(ethylene succinate) and poly(butylene succinate); thermoplastic resins such as polyolefin resins such as polypropylene and polyethylene, polyimide resins, polyarylate resins, and mixtures thereof; and among these, films made of polyester, polyamide, polyethylene, and polypropylene can be preferably used. These substrate films may be unstretched or stretched films, and the manufacturing method is not limited. The thickness of the substrate film is not particularly limited, but is usually within the range of 1 to 500 μm. The printed surface of the substrate film is preferably subjected to a corona discharge treatment. Silica, alumina, etc. may be vapor-deposited.
[0088] Alternatively, it may be a laminate in which a paper substrate and a plastic film are laminated together. In this case, the position of the printed layer (ink coating) on which the liquid ink of the present invention is printed is not particularly limited, but it is preferable to provide an ink coating on a paper substrate and place the ink coating on the inside of the laminate, that is, to form a laminate in which the surface on which the ink coating is provided is overlapped with a plastic film. EXAMPLES
[0089] The present invention will be described in more detail below with reference to examples. In the examples, "parts" means "parts by mass" and "%" means "% by mass". The measurement methods for each measurement value were as follows.
[0090] (glass transition temperature) The glass transition temperature (Tg) was measured using a differential scanning calorimeter ("DSC Q100" manufactured by TA Instruments, Inc.) by scanning in a nitrogen atmosphere using a cooling device at a temperature range of -80 to 450°C and a heating rate of 10°C / min.
[0091] (Weight average molecular weight (Mw)) The weight average molecular weight was measured by gel permeation chromatography (GPC) under the following conditions. Measuring device: Tosoh Corporation HLC-8220 Column: Tosoh Corporation guard column HXL-H + Tosoh Corporation TSKgel G5000HXL + Tosoh Corporation TSKgel G4000HXL + Tosoh Corporation TSKgel G3000HXL + Tosoh Corporation TSKgel G2000HXL Detector: RI (differential refractometer) Data processing: Tosoh Corporation SC-8010 Measurement conditions: Column temperature 40℃ Solvent Tetrahydrofuran Flow rate 1.0ml / min Standard: Polystyrene Sample: 100 μl of tetrahydrofuran solution containing 0.4% by mass of resin solids filtered through a microfilter
[0092] (Acid value) The acid value was measured in accordance with JIS test method K 0070-1992 by dissolving 0.5 g of the polymer in a tetrahydrofuran (THF) solvent and titrating with a 0.1 M alcoholic solution of potassium hydroxide using phenolphthalein as an indicator. (Average particle size of synthetic wax) The average particle size of the synthetic wax was calculated from the frequency distribution measured using a scanning electron microscope S-3400N manufactured by Hitachi, Ltd. The softening point of the synthetic wax was measured using the ring and ball method (based on JIS K7234-86, heating rate 5°C / min).
[0093] (Synthesis Example 1: Dispersion of styrene-acrylic copolymer and polysaccharide complex (AB-1)) A reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, a dropping funnel and a nitrogen inlet tube was charged with 500 parts of isopropyl alcohol, and stirring was started, and the temperature was raised to 80 ° C. Here, under a nitrogen stream, 91 parts of monomers in a ratio of styrene / α-methylstyrene / butyl acrylate / acrylic acid / methyl methacrylate / 2-ethylhexyl acrylate = 40 / 15 / 10 / 10 / 20 / 5, 109 parts by mass of Oji Ace (manufactured by Oji Cornstarch Co., Ltd., oxidized starch with a carboxyl group substitution degree of 0.03, moisture content 12.5 mass%), and 4 parts of t-butylperoxy-2-ethylhexanoate were continuously dropped over 0.5 hours to obtain a mixture 1 in which a styrene-based monomer and a (meth)acrylic monomer were copolymerized.
[0094] 5 parts of ammonia was added to 100 parts of the mixture 1, and a mixture of 1 part of polypropylene glycol PPG#1300 and 144 parts of ion-exchanged water was added dropwise at a rate of 5 ml per minute while stirring to obtain a mixture 2. The methyl ethyl ketone and isopropyl alcohol were removed from the obtained mixture 2 using a rotary evaporator to obtain a dispersion of a complex (AB-1) of a styrene-acrylic copolymer and a polysaccharide. The weight-average molecular weight of the complex (AB-1) was 200,000, the acid value was 20, and the glass transition temperature was -18°C. The solid content of the dispersion (AB-1) was 40%, and the biomass degree was 50.
[0095] (Synthesis Example 2: Dispersion of Styrene-Acrylic Copolymer (A-1)) 500 parts of isopropyl alcohol was charged into a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, a dropping funnel, and a nitrogen inlet tube, and stirring was started, and the temperature was raised to 80° C. 96 parts of monomers with a ratio of styrene / α-methylstyrene / butyl acrylate / acrylic acid / methyl methacrylate / 2-ethylhexyl acrylate=40 / 15 / 10 / 10 / 20 / 5 and 4 parts of t-butylperoxy-2-ethylhexanoate were continuously dropped into the reaction vessel under a nitrogen stream over 0.5 hours to obtain a mixture 3 in which a styrene-based monomer and a (meth)acrylic monomer were copolymerized.
[0096] 5 parts of ammonia was added to 100 parts of the mixture 3, and a mixture of 1 part of polypropylene glycol PPG#1300 and 32 parts of ion-exchanged water was added dropwise at a rate of 5 ml per minute while stirring to obtain a mixture 4. Methyl ethyl ketone and isopropyl alcohol were removed from the obtained mixture 4 using a rotary evaporator to obtain a dispersion of a styrene-acrylic copolymer (A-1). The weight-average molecular weight of the copolymer (A-1) was 200,000, the acid value was 30, and the glass transition temperature was 2°C. The solid content of the copolymer (A-1) was 40%, and the biomass degree was 0.
[0097] Example 1 A mixture of the pigment (phthalocyanine blue), alkali-soluble water-based acrylic resin, and water shown in Table 1 was milled in a bead mill to prepare a milled base ink, which was then adjusted to the final composition shown in Table 1 to prepare the water-based liquid ink of Example 1. The viscosity of the obtained water-based liquid ink was adjusted with water to 16 seconds (25°C) using a Zahn cup #4 (manufactured by Rigo Co., Ltd.) to make a flexographic printing ink.
[0098] [Examples 2 to 21, Comparative Examples 1 to 4] Similarly to Example 1, the water-based liquid inks of Examples 2 to 21 and Comparative Examples 1 to 4 were prepared according to the compositions shown in the table below, and the viscosity of the water-based liquid ink was adjusted with water to 16 seconds (25°C) using a Zahn cup #4 (manufactured by Rigo Co., Ltd.) to prepare flexographic printing inks.
[0099] The details in the table are as follows: Phthalocyanine blue: FASTGEN BLUE LA5380 (Phthalocyanine blue pigment: manufactured by DIC Corporation) Titanium oxide: JR-600A (manufactured by Teika Co., Ltd.) Alkali-soluble water-based acrylic resin: JONCRYL678 (BASF Ltd.), acid value 215, glass transition temperature 85°C, solid content 25% Starch derivative (B): Oji Ace (manufactured by Oji Cornstarch Co., Ltd.), oxidized starch with a carboxyl group substitution degree of 0.03, moisture content of 12.5% by mass Styrene-acrylic copolymer emulsion (A-2): JONCYL8052 (BASF Ltd.), acid value 65, glass transition temperature 21°C, solid content 47% Urethane resin: Hydran WLS-201K (DIC Corporation), solid content 40% Alkali-soluble water-based rosin resin (neutralized with ammonia): Harimac AS-5 (Harima Chemicals Co., Ltd.), acid value 190, softening point 160°C, solid content 40% Polyethylene wax (C): Chemipearl W-400, manufactured by Mitsui Chemicals, Inc. (average particle size 3 μm, manufactured by Mitsui Chemicals, Inc.), solid content 40%
[0100] The viscosity-adjusted flexographic printing inks of Examples 1 to 19 and Comparative Examples 1 to 4 were printed on uncoated paper (thin paper, basis weight 21 g / m) using a Flexoproof100 test printing machine (manufactured by Testing Machines, Inc., anilox 200 lines / inch). 2 A solid pattern measuring 280 mm in height and 100 mm in width was printed on the paper, which was then dried with a hair dryer to obtain a print.
[0101] In addition, for the adhesion test, in addition to the uncoated paper mentioned above, coated paper (oil-resistant coated paper, basis weight 200 g / m 2 Printed on coated side), polyethylene laminated paper (MDPE / paper / LDPE, basis weight 300g / m 2 The other tests were carried out on uncoated paper.
[0102] The obtained prints were evaluated as follows. (Evaluation item 1: Adhesion) After leaving the print for one day, cellophane tape (12 mm wide, made by Nichiban) was applied to the printed surface, and one end of the cellophane tape was quickly pulled off perpendicular to the printed surface. The remaining percentage of the printed film was visually evaluated based on the area ratio. ⊚: The printing film did not peel off at all, or the base paper was torn. ○: 80% to less than 90% of the printing film remained on the base paper. △: 50% to less than 80% of the printing film remained on the base paper. ×: Less than 50% of the printing film remained on the base paper.
[0103] (Evaluation item 2: Heat resistance) The ink was applied to uncoated paper using bar coater #2 and left for 24 hours to produce a print. Next, using a heat seal tester equipped with a hot plate with a thermal gradient of 80 to 200°C, the printed surface was pressed against aluminum foil and between printed surfaces at a pressure of 2.0 kg / cm2 for 1 second. Heat resistance was evaluated based on the minimum temperature at which the ink on the printed surface transferred to the aluminum foil. A rating of 4 or higher is within the practical range. (Evaluation Criteria) 5: Over 180℃. 4: Above 160℃ and below 180℃. 3: Above 140°C and below 160°C. 2: Above 120℃ and below 140℃. 1: Below 120℃.
[0104] (Evaluation item 3: Water resistance) The surface of the ink coating was rubbed back and forth with a cotton swab moistened with water once, and the degree of damage to the ink coating was judged after 50 round trips. ◎: No scratches on the coating after 50 passes. ○: After 50 round trips, the coating film was slightly scratched. △: After 50 strokes, slight scratches were observed on the coating film. ×: The base coat becomes visible after 50 passes.
[0105] (Evaluation item 4: Oil resistance) The surface of the ink coating was rubbed back and forth with a cotton swab moistened with oil once, and the degree of damage to the ink coating was judged after 20 round trips. ◎: No scratches on the coating after 20 passes. ○: After 20 round trips, the coating film was slightly scratched. △: After 20 round trips, slight scratches were observed on the coating film. ×: The base coat is visible after 20 passes.
[0106] (Evaluation item 5: Abrasion resistance) The prints were cut into 2.5 x 25 cm pieces to prepare test pieces, and using a Gakushin type friction tester (manufactured by Daiei Scientific Instruments Manufacturing Co., Ltd.), a piece of high-quality paper was placed against the printed coating surface of the prints as a backing paper, and the prints were rubbed 100 times with a load of 200 g. The ink coating after rubbing was then visually evaluated according to the following evaluation criteria. ⊚: The ink film was not damaged at all. ◯: Damage to 25% or less of the ink film was observed. △: Damage to more than 25% and up to 50% of the ink coating was observed. ×: Damage to more than 50% of the entire ink coating was observed.
[0107] (Evaluation item 6: Water and friction resistance) The printed material was cut into 2.5 x 25 cm test pieces and, using a Gakushin type friction tester (manufactured by Daiei Scientific Instruments Manufacturing Co., Ltd.), a piece of water-soaked Kanakin was placed against the printed coating of the printed material as a backing paper and rubbed 10 times with a load of 200g. The degree of damage to the ink coating after rubbing was visually evaluated according to the following evaluation criteria. ⊚: The ink film was not damaged at all. ◯: Damage to 25% or less of the ink film was observed. △: Damage to more than 25% and up to 50% of the ink coating was observed. ×: Damage to more than 50% of the entire ink coating was observed.
[0108] (Evaluation item 7: Oil friction resistance) The printed material was cut into 2.5 x 25 cm pieces to prepare test pieces. Using a Gakushin type friction tester (manufactured by Daiei Scientific Instruments Manufacturing Co., Ltd.), a piece of oil-soaked Kanakin was placed against the printed coating of the printed material as a backing paper, and the test piece was rubbed 10 times with a load of 200 g. The degree of damage to the ink coating after rubbing was visually evaluated according to the following evaluation criteria. ⊚: The ink film was not damaged at all. ◯: Damage to 25% or less of the ink film was observed. △: Damage to more than 25% and up to 50% of the ink coating was observed. ×: Damage to more than 50% of the entire ink coating was observed.
[0109] (Evaluation item 8: Heat and friction resistance) The prints were cut into 2.5 x 25 cm pieces to prepare test pieces, and using a Gakushin type friction tester (manufactured by Daiei Scientific Instruments Manufacturing Co., Ltd.), a piece of fine paper was placed against the printed coating surface of the prints as a backing paper, and the prints were rubbed 50 times at 80°C with a load of 200 g. The ink coating after rubbing was visually evaluated according to the following evaluation criteria. ⊚: The ink film was not damaged at all. ◯: Damage to 25% or less of the ink film was observed. △: Damage to more than 25% and up to 50% of the ink coating was observed. ×: Damage to more than 50% of the entire ink coating was observed.
[0110] (Evaluation item 9: Whiteness measurement) The ink was applied to uncoated paper using a bar coater #12 and left for 24 hours to produce a print. The hue (Lab value) of the ink coating of the print was then measured under the following conditions. Colorimeter: X-Rite eXact Lab measurement: D50 / 2° L*: Represents the lightness of the color. The closer to 100, the whiter the color. a*: represents the red-green position. The closer to 0, the whiter b*: represents the yellow-blue level. The closer to 0, the whiter Status: E Reference color (uninked coated paper): (L0:93:45, a0:0.44, b0:0.39) Sample color (ink coating example): (L1: 95: 25, a1: -0.28, b1: 2.46) Sample color (ink coating comparison example): (L1: 95: 06, a1: -0.31, b1: 4.35) The composition and evaluation results are shown in the table below.
[0111] [Table 1]
[0112] [Table 2]
[0113] [Table 3]
[0114] [Table 4]
[0115] From the table, it is clear that the examples provide liquid ink compositions that achieve a high biomass content, have high adhesion to the substrate, and are excellent in oil resistance, water resistance, heat resistance, and abrasion resistance. In addition, the b* value in the whiteness measurement shows that the liquid inks of the examples have less yellowing than the liquid inks of the comparative examples.
Claims
1. A binder having a styrene-(meth)acrylic copolymer (A) component portion and a polysaccharide (B) component portion; Contains a lubricant (C), the binder is a styrene-(meth)acrylic copolymer (A) having a modified polysaccharide (B) added thereto; The water-based liquid ink is characterized in that the glass transition point of the copolymer (A) is in the range of -40°C to 40°C.
2. An aqueous liquid ink as described in claim 1, wherein the total amount of binder contained in the aqueous liquid ink is 60 mass% or more of the styrene-(meth)acrylic copolymer (A) to which the modified polysaccharide (B) has been attached.
3. 3. The water-based liquid ink according to claim 1, further comprising a colorant and an aqueous medium.
4. The aqueous liquid ink according to any one of claims 1 to 3, wherein the polysaccharide (B) is at least one selected from the group consisting of carrageenan, galactomannan, xanthan gum alginate, pectin, xylan, glucomannan, pullulan, curdlan, cellulose, cellulose derivatives, carboxymethylcellulose (CMC), starch, starch derivatives, and corn starch.
5. The water-based liquid ink according to any one of claims 1 to 4, wherein the lubricant (C) is a hydrocarbon wax.
6. The water-based liquid ink according to any one of claims 1 to 5, wherein the acid value of the copolymer (A) is in the range of 1 to 250 mgKOH / g.
7. The water-based liquid ink according to any one of claims 1 to 6, further comprising another resin as a binder.
8. The water-based liquid ink according to any one of claims 1 to 6, further comprising an auxiliary.
9. The water-based liquid ink according to any one of claims 1 to 8, wherein the polysaccharide (B) is contained in an amount of 10 to 80 mass % based on the total amount of solids in the ink.
10. The water-based liquid ink according to any one of claims 1 to 9, which is applied to flexographic printing or gravure printing.
11. A printed matter comprising a substrate and the water-based liquid ink according to any one of claims 1 to 10 printed thereon.
12. A greaseproof paper having a paper base material printed with the water-based liquid ink according to any one of claims 1 to 10.
13. A laminate comprising a plastic substrate and the printed matter according to claim 11 or the grease-resistant paper according to claim 12 laminated together with the ink coating film disposed on the inner side.
Citation Information
Patent Citations
Printing ink composition
JP2012207130A
Aqueous flexographic printing ink composition
JP2016180061A
Aqueous flexographic printing ink composition
JP2019108529A
Aqueous flexographic printing ink composition
JP2019108530A
Water-based flexographic ink and printed matter
JP2021167377A